1996
DOI: 10.1021/jm950913h
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Studies of 6-Substituted Decahydroisoquinoline-3-carboxylic Acid AMPA Receptor Antagonists. 2. Effects of Distal Acid Bioisosteric Substitution, Absolute Stereochemical Preferences, and in Vivo Activity

Abstract: We have explored the excitatory amino acid antagonist activity in a series of decahydroiso-quinoline-3-carboxyic acids, and within this series found the potent and selective AMPA antagonist (3SR,4aRS,6RS,8aRS)-6-(2-(1H-tetrazol-5-yl )ethyl) decahydroisoquinoline-3-carboxylic acid (1). In this and the preceding paper, we looked at the structure-activity relationships for AMPA antagonist activity in this series of compounds. We have already shown that 1 had the optimal stereochemical array and that AMPA antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Crystal structures have not yet been reported for ligands from the extensive series of decahydroisoquinolines which have been developed as glutamate receptor antagonists (Clarke et al, 1997; Ornstein et al, 1996; Ornstein et al, 1992; Weiss et al, 2006). Of this series we chose to study LY466195, one of the most potent GluK1 antagonists reported to date.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures have not yet been reported for ligands from the extensive series of decahydroisoquinolines which have been developed as glutamate receptor antagonists (Clarke et al, 1997; Ornstein et al, 1996; Ornstein et al, 1992; Weiss et al, 2006). Of this series we chose to study LY466195, one of the most potent GluK1 antagonists reported to date.…”
Section: Resultsmentioning
confidence: 99%
“…administration of ATPA, the tert -butyl analogue of AMPA. In previous studies, ATPA was identified as an AMPA agonist (Ornstein et al, 1996), but was later discovered to be a selective agonist of the GluK1 (formerly GluR5) kainate receptor (Hoo et al, 1999; Jane et al, 2009). In the present study, ATPA (30 mg/kg, i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of the tetrazole with a sulphonyltriazole moiety resulted in an enhancement of potency and selectivity for AMPA receptors (ICso = 0.16 ± 0.79,umol/1 for antagonism of AMPA-mediated depolarizations in the cortical wedge assay) (ORNSTEIN et al 1996b). The activity was found to reside in the (-)- (3 S,4aR,6 S,8aR)-isomer (ICso 0.6,umolll for displacement of [3H]AMPA binding).…”
Section: Decahydroisoquinoiinesmentioning
confidence: 99%
“…Thus it would appear that the decahydroisoquinoline ring imposes a unique conformation on the molecule. It was observed that for both C-6 epimers it is the compound with the S absolute stereochemistry at C-3 which has the AMPA receptor antagonist activity (ORNSTEIN et al 1996b). This contrasts with observation that for the decahydroisoquinoline series of NMDA receptor antagonists the activity was found to reside in the isomer with R absolute stereochemistry at C-3.…”
Section: Decahydroisoquinoiinesmentioning
confidence: 99%